DECARBONISATION OF INDUSTRIAL GAS EMISSIONS BY ADSORPTION METHODS - Vira Sabadash; Oleksiy Lopushansky (Environmental Problems)
The article is dedicated to the problem of decar-bonising industrial gas emissions using adsorption methods. The article examines promising approaches to reducing carbon dioxide (CO2) emissions using adsorption materials with high selectivity and efficiency in capture processes. The purpose of the study is to determine the adsorption capacity of various types of adsorbents, including synthetic and natural materials, in particular, fly ash synthesised by the hydrothermal method, zeolite obtained by the sintering method, natural zeolite, and fly ash from thermal power plants. The research showed that the most effective adsorbent for absorbing CO2 is zeolite syn-thesised by hydrothermal, demonstrating a high adsorption capacity among the studied materials. Natural zeolite and thermal power plant fly ash have a much lower adsorption capacity, but they can be used as cost-effective alternatives for processes with moderate performance requirements. The study also highlights the importance of selecting adsorbents depen-ding on operating conditions, such as temperature and pressure, which affect adsorption. According to the research results, synthetic zeolites have a significant advantage in adsorption efficiency due to their high specific surface area and porous structure, which allow effective absorption of CO2 even at relatively low gas concentrations. The generalised conclusions of the article indicate that the use of adsorption methods for decarbonising industrial emissions can significantly reduce the level of greenhouse gases in the atmosphere. This research has the potential to significantly impact the field of environmental science and engineering, providing valuable insights for future studies and practical applications.